Organizational Restructuring to Enhance Strategic Capabilities in Educational Institutions: A Case Study of the Phuket Campus Office Prince of Songkla University - Jaitrong, Naraphat; Chorkaew, Supaporn; Kanadphol, Anisa; Nhukong, Pimlapat (Ratchaphruek Journal, 2025)
This qualitative research aimed to explore organizational restructuring approaches essential for enhancing the strategic capacity of administrative operations at the Phuket Campus of Prince of Songkla University. Data were collected via in-depth interviews using a semi-structured guide, involving 39 participants: 16 purposively selected administrators/supervisors and 23 conveniently selected administrative staff. Data analysis utilized content analysis and descriptive interpretation. The findings identified five key components critical for strategic organizational restructuring: 1) Flexibility and Agility: Enhancing operational flexibility by reducing redundancy and increasing agility, 2) Digital Integration: Leveraging digital technologies to improve efficiency and transparency in work processes, 3) Competency and Alignment: Developing personnel competencies and aligning resources with strategic objectives, 4) Workforce Management: Managing workload balance while fostering motivation and organizational engagement, and 5) Innovation and Collaboration: Improving communication and integrating innovations to promote cross-functional collaboration. These components were synthesized into the FLEXI Model, a conceptual framework designed to enhance strategic capacity and support sustainable operations, enabling the organization to effectively adapt to future dynamic environmental changes.